Breaking bad. The fifth season - Cranston, Bryan, 1956-; Gunn, Anna, 1968-; Paul, Aaron, 1979-; Norris, Dean; Mitte, R. J.; Brandt, Betsy; Sony Pictures Television; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2013)
Walter White, a one-time mild-mannered chemistry teacher whose transformation into a deadly criminal kicks into overdrive.
Disc 1. Live free or die ; Madrigal ; Hazard pay -- disc 2. Fifty-one ; Dead freight ; Buyout -- disc 3. Say my name ; Gliding over all.
Originally broadcast as single episodes of a television program in 2012.
Bonus features: "Chicks 'n' guns," a newly produced exclusive scene; three uncensored episodes; deleted & extended scenes; gag reel; behind-the-scenes of "Chicks 'n' guns;" cast and crew commentaries; featurettes; prison stunt rehearsal; "Writers' room timelapse;" Jesse Plemons & Laura Fraser audition footage; Gallery 1988 art show; Chris Hardwick's All-Star Celebrity Bowling; 19 episodes of "Inside Breaking Bad."
Anna Gunn, Bryan Cranston, Aaron Paul, Dean Norris, Betsy Brandt, RJ Mitte.
Rating: TV14.
DVD; NTSC, region 1; widescreen (1.78:1) presentation; English 5.1 Dolby digital, French (PAR) Dolby surround.
English or French dialogue; closed-captioned.
Keywords: Cancer -- Patients -- Drama; Chemistry teachers -- Drama; Drug dealers -- Drama; Chemistry -- Drama; Criminal behavior -- Drama; Drug traffic -- Drama; Terminally ill -- Drama; Crime -- Drama; Methamphetamine -- Economic aspects -- Drama; Drug dealers -- Family relationships -- Drama; Ice (Drug) -- Drama; Television crime shows; Video recordings for the hearing impaired; Fiction television programs